A Study of ZSM-5 Molecular Sieve Shaping for an Innovative Cyclohexene Hydration Process - Wang, Baohe; Jin, Dianyi; Zhang, Zhaobang; Ai, Zihan; Zhu, Jing (Bulletin of Chemical Reaction Engineering & Catalysis, 2024)
The development of the zeolite molecular sieves (ZSM-5) molding technique is essential for the cyclohexene hydration reaction distillation process in both industrial and research settings. The reactive distillation process can solve many of the drawbacks associated with the existing technique of manufacturing cyclohexanol via cyclohexene hydration, such as high catalyst digestibility, low conversion rate, and operational challenges. This study developed a series of molded ZSM-5 catalysts with various binder types and contents were constructed. The suggested pseudo-boehmite and hydroxypropyl methylcellulose were chosen as binders for extrusion molding of ZSM-5. The effects of binders on the strength reliability were investigated by strength tests and statistical analysis of the Weibull function. The effects of binders on the physical structure, acidity, and catalytic performance of ZSM-5 were investigated by X-ray diffraction, scanning electron microscopy, physical adsorption of N2, and desorption of NH3. The findings demonstrate that the addition of binder has no effect on ZSM-5's crystal structure. The experiment's results showed that the molded catalyst could be used for the hydration process with over 95% selectivity and a yield of 10.45% cyclohexanol. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).